Exploring the networked image in 'post' art practices. Issue 2 (1st December 2018) - Lynch, Garrett
This article presents and discusses a series of four networked artworks undertaken since 2013. The artworks are performative, created within the web over a duration of time, are visible to an audience throughout their creation and as such can be considered as durational networked performances. Different in subject matter they overlap considerably in the themes, form and methods employed and constitute a body of research that explores the networked image in relation to a number of 'post' art practices. Specifically, this includes the questioning of media and form through postmedia, post-photographic, post-digital, post-Internet and post-screen practices in addition to addressing the manner in which the artist creates through postdisciplinary and postproduction methods.